Hybrid simulation model supporting efficient computations within rail traffic simulations - Novotný, Radek; Kavička, Antonín (Dime University of Genoa, 2019)
The contribution deals with the unitary hybrid simulation model of railway traffic, which applies different levels of abstraction (microscopic and macroscopic) to different parts of the simulating system. As a result of applying this approach, simulation experiments can reflect the traffic within a large part of the railway network. The entire computational complexity is supposed to be significantly lower in comparison with an application of a pure microscopic simulator. From this point of view, the hybrid model can also be used to optimize the design of simulators of large and complex railway systems. Special attention is paid to stochastic simulation experiments (applying random train delays) and to transforming train flows at the interface between pairs of microscopic and macroscopic submodels.
Hybridní simulační model podporující efektivní návrh v rámci simulací železničního provozu
Keywords: scalable simulation model; unitary hybrid model; railway traffic; transformation of traffic flows; random train delays; škálovatelný simulační model; unitární hybridní model; železniční provoz; transformace dopravních proudů; náhodná zpoždění